(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The focus of this paper is on how dividend payments affect the value of a company. Creating asustainable dividend policy is a difficult but crucial responsibility for every manager. Stock prices risewhen dividends are distributed. The dividend is something the corporation strives for constantly. If thecompany wants to stay afloat, it needs to implement a consistent dividend policy that will keep investorshappy and drive up the share price. The report analyzes data from 34 NIFTY 50 companies. You’ll findbusinesses from the banking industry (eight firms), the auto industry (five firms), the energy sector (eightfirms), the pharmaceutical industry (four firms), the IT industry (five firms), and the metal industry (fivefirms) (4 companies). The research spans the fifteen-year period from the 2004-05 to the 2018-19academic years. Obtaining the necessary information from the Prowess database. Increasedproductivity, profitability, and share market value are just some of the benefits these industries will seeas a direct result of the study’s findings. A company’s dividend policy sends a message to its investorsabout the company’s health and growth, making it a crucial component of corporate finance. Thedividend payout ratio and the amount of earnings retained by a company are directly related to thedividend choice made by the company, which is determined by the firm’s dividend policy. Differentfactors, such as firm size, ownership, and other factors, influence the dividend decision. The study’sgoal is to examine the effects of dividend policy on the financial health and stock value of chosencompanies. Secondary information was gathered from the prowess database.